2016
DOI: 10.1002/2015jg003233
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the metabolic potential of microbial communities in ultra‐basic, reducing springs at The Cedars, CA, USA: Experimental evidence of microbial methanogenesis and heterotrophic acetogenesis

Abstract: Present-day serpentinization generates groundwaters with conditions (pH > 11, Eh < À550 mV) favorable for the microbial and abiotic production of organic compounds from inorganic precursors. Elevated concentrations of methane, C 2 -C 6 alkanes, acetate, and formate have been detected at these sites, but the microbial or abiotic origin of these compounds remains unclear. While geochemical data indicate that methane at most sites of present-day serpentinization is abiogenic, the stable carbon, hydrogen, and clum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 54 publications
1
44
0
Order By: Relevance
“…Isotopically labeled experiments showed that most of the CO was oxidized, and little was incorporated into microbial lipids. Methanogenesis , both autotrophic and heterotrophic, was demonstrated using 13 C‐labeled substrates in laboratory experiments with samples from the serpentinizing system at The Cedars [ Kohl et al ., ]. Substrates converted to methane included bicarbonate, methanol, formate, and acetate.…”
Section: Molecular Evidence For Microbial Metabolisms From Hyperalkalmentioning
confidence: 99%
“…Isotopically labeled experiments showed that most of the CO was oxidized, and little was incorporated into microbial lipids. Methanogenesis , both autotrophic and heterotrophic, was demonstrated using 13 C‐labeled substrates in laboratory experiments with samples from the serpentinizing system at The Cedars [ Kohl et al ., ]. Substrates converted to methane included bicarbonate, methanol, formate, and acetate.…”
Section: Molecular Evidence For Microbial Metabolisms From Hyperalkalmentioning
confidence: 99%
“…The Cedars is an active serpentinization site located in northern California (Barnes et al, 1967) with spring waters that have extremely high pH (~12), very low E h (~−500 mV or less) and are rich in Ca 2+ (~1 mM), hydrogen and methane gas, and contain very low levels of dissolved organic carbon, total inorganic carbon, ammonium, phosphate and electron acceptors (oxygen, nitrate, sulfate) (Morrill et al, 2013;Kohl et al, 2016). While these properties describe an environment that should be exceptionally challenging for microbial life, our previous studies have revealed a diverse microbial community associated with these ultrabasic springs (Suzuki et al, 2013), several of the members of which are now in culture (Suzuki et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…With this in mind, some of these sites, specifically the Oman ophiolite, have been proposed for enhanced carbon capture storage that would involve injecting CO 2 to enhance carbon sequestration (Kelemen and Matter 2008). However, a recent study has also shown that under certain conditions CO 2 can be converted to CH 4 microbially at the Cedars (Kohl et al 2016). Therefore, before we focus on ways to modify these systems to enhance CO 2 sequestration we must first gain a better understanding of the natural baseline of the sites and their impacts on the environment as a whole.…”
Section: Natural Global Warming Potentialmentioning
confidence: 99%
“…However, while sites of serpentinization often lead to abiogenic CH 4 production, these sites can also feature thermogenic and/or microbial CH 4 (Brazelton et al 2006;Kelley et al 2005;Morrill et al 2013;Szponar et al 2013). For example, microbial CH 4 has been proposed for samples in the Precambrian shield (Canada) (Sherwood Lollar et al 1993) , the Lost City Vents (Mid Atlantic Ocean) (Kelley et al 2005) and at the Cedars (United States) Kohl et al 2016). In addition, if sedimentary organic matter is present beneath the serpentinizing ultramafic body then thermogenic CH 4 is also a possibility.…”
mentioning
confidence: 99%